2015
DOI: 10.1111/petr.12469
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of bone metabolism in children with renal transplantation

Abstract: This study aims to evaluate BMD and bone biomarkers and to investigate the effects of immunosuppressives on bone disease after RTx. Thirty-three RTR aged 16.7 ± 3.7 yr and healthy controls (n = 32) were enrolled. There was no difference between pre-RTx BMD and BMD at the time of study (45.9 ± 30.9 months after RTx), while both values were lower than controls (p < 0.01 and p < 0.05, respectively). Worst BMD scores were obtained at sixth month after RTx (-0.2 ± 0.9) and best at fourth year (1.4 ± 1.3). 25-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A population‐based prospective study reported that the incidence of all fractures was 6‐fold higher and the incidence for vertebral fractures was 160‐fold higher in the study group in comparison with the control population . Although there is compelling knowledge about optimization of bone health in pediatric transplant recipients, previous studies have consequently emphasized continued efforts of clinical research for improving bone health of this population …”
Section: Introductionmentioning
confidence: 99%
“…A population‐based prospective study reported that the incidence of all fractures was 6‐fold higher and the incidence for vertebral fractures was 160‐fold higher in the study group in comparison with the control population . Although there is compelling knowledge about optimization of bone health in pediatric transplant recipients, previous studies have consequently emphasized continued efforts of clinical research for improving bone health of this population …”
Section: Introductionmentioning
confidence: 99%